The situation of Polish prisoners of war and refugees in Turkestan in 1914–1923 - Doroshenko, Tat’yana I. (Journal of the Belarusian State University. History, 2023)
Based on the analysis of various sources extracted from the archives of Uzbekistan, as well as periodicals, the article attempts to analyse the transformation of the situation of Polish prisoners of war and refugees in Turkestan during the World War I. The scientific novelty of the study lies in the fact that the author, for the first time on the materials of the archives of Uzbekistan, many of which are being introduced into scientific circulation for the first time, tries to describe the problem of Polish refugees and prisoners of war in Turkestan in a difficult historical period – the period of the World War I and two revolutions of 1917, and also highlight the process of reevacuation to the Motherland. The chronological framework of the study covers the period of 1914 – the beginning of the World War I, when prisoners of war began to be sent to Turkestan, and 1923 – when the reevacuation of Polish prisoners of war and refugees was actually completed. The practical significance of the study lies in the fact that it can be used when writing a textbook on the history of Uzbekistan and when giving lectures to students of the universities of the republic.
Keywords: Turkestan; Poles; World War I; prisoners of war; refugees; revolution; reevacuation